Rereading the sixties. Reconsidering planning as a vehicle for structural change - Albrechts, Louis (European Spatial Research and Policy, 1994)
In the 1960s the planning discipline had a strong profile and identity. Today, after thirty years in many countries, much of this profile and professional identity has disappeared. Nevertheless important groups in society call for a clear break with existing policies. This paper reflects whether planning can be used as a vehicle to induce such change in a democratic way. It is argued that the 1960s provided some basic ideas in this respect. Criticism formulated against the often very naive way these concepts have been implemented must be acknowledged. Especially the ideas elaborated by Jantsch, Ozbekhan and de Jouvenel provide concepts that allow us to define a type of planning that is at once integrative in its approach, European in its orientation, political in its attitude towards power structures, normative in purpose, innovative in its search for solutions and entrepreneurial in scope. These concepts will be summarily dealt with and linked with an ongoing spatial planning experiment.